(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This part of the article explores the institutional and geopolitical factors contributing to cross-border political instability in the Fergana Valley during the decade 2015–2025. It focuses on the governance gap that emerged after the collapse of the Soviet Union, emphasizing how the absence of clearly demarcated borders, weak intergovernmental coordination, and fragile local institutions have aggravated disputes among Kyrgyzstan, Tajikistan, and Uzbekistan. The article highlights how smuggling, militarized borders, and inconsistent water-sharing policies created flashpoints for conflict. Despite these challenges, the analysis also recognizes positive trends, including Uzbekistan’s diplomatic turn toward regional cooperation post-2016 and the 2025 Kyrgyz-Tajik border agreement. The findings suggest that sustainable stability in the Fergana Valley depends on institutional reform, inclusive governance, and regionally coordinated frameworks for conflict prevention and resource management.